No Surgical Innovation Without Evaluation: Evolution and Further Development of the IDEAL Framework and Recommendations. Issue 2 (February 2019) - Hirst, Allison; Philippou, Yiannis; Blazeby, Jane; Campbell, Bruce; Campbell, Marion; Feinberg, Joshua; Rovers, Maroeska; Blencowe, Natalie; Pennell, Christopher; Quinn, Tom; Rogers, Wendy; Cook, Jonathan; et al.
Abstract : Objective: To update, clarify, and extend IDEAL concepts and recommendations. Background: New surgical procedures, devices, and other complex interventions need robust evaluation for safety, efficacy, and effectiveness. Unlike new medicines, there is no internationally agreed evaluation pathway for generating and analyzing data throughout the life cycle of surgical innovations. The IDEAL Framework and Recommendations were designed to provide this pathway and they have been used increasingly since their introduction in 2009. Based on a Delphi survey, expert workshop and major discussions during IDEAL conferences held in Oxford (2016) and New York (2017), this article updates and extends the IDEAL Recommendations, identifies areas for future research, and discusses the ethical problems faced by investigators at each IDEAL stage. Methods: The IDEAL Framework describes 5 stages of evolution for new surgical therapeutic interventions—Idea, Development, Exploration, Assessment, and Long-term Study. This comprehensive update proposes several modifications. First, a "Pre-IDEAL" stage describing preclinical studies has been added. Second we discuss potential adaptations to expand the scope of IDEAL (originally designed for surgical procedures) to accommodate therapeutic devices, through an IDEAL-D variant. Third, we explicitly recognise the value of comprehensive data collection through registries at all stages in the Framework and fourth, we examine the ethical issues that arise at each stage of IDEAL and underpin the recommendations. The Recommendations for each stage are reviewed, clarified and additional detail added. Conclusions: The intention of this article is to widen the practical use of IDEAL by clarifying the rationale for and practical details of the Recommendations. Additional research based on the experience of implementing these Recommendations is needed to further improve them. Abstract : Supplemental Digital Content is available in the text